The contribution of corporate policies to the creation of competitive advantage: the case of the Unimed de Paranavaí corporate organization - Colla, Julio Ernesto; Bueno Nascimento, Gláucia; Ferreira dos Reis, Júlio; Lauermann Koch, Leani (REBRAE, 2016)
In the competitive global context, organizations in a sector are seeking to develop different strategies to stand out from their competitors. Thus, they seek organizational policies as plans of action to achieve a sustainable competitive advantage. Therefore, the main objective of the present study is to analyze corporate policies and their contribution to the creation of sustainable competitive advantage in a cooperative organization. The object of study is Unimed de Paranavaí, in Paraná State. The research is predominantly descriptive and qualitative. The data were collected through semi-structured interviews and non-participant observation, with a sample of employees of the Administrative area and Personnel Department of the organization in question. According to the data analysis, the results show the importance of corporate policies in organizations, as Unimed has established flexible, comprehensive, coordinated and ethical policies. All the stakeholders are involved in the decision-making process, which is very important and helps the organization to generate a form of competitive advantage.